Species-specific associations between overstory and understory tree species in a semideciduous tropical forest - Flaviana Maluf Souza; Sergius Gandolfi; Ricardo Ribeiro Rodrigues (Acta Botânica Brasílica, 2015)
We investigated the occurrence of associations between overstory and understory tree species in a semideciduous tropical forest. We identified and measured all trees of nine canopy species with diameter at breast height ≥4.8 cm in a 10.24 ha plot and recorded all individuals beneath their canopies ("understory individuals") within the same diameter class. The total density of understory individuals did not significantly differ under different overstory species. One overstory species (Ceiba speciosa) showed higher understory species richness compared with five other species. There was a strong positive association between three overstory species (Esenbeckia leiocarpa, Savia dictyocarpa, and C. speciosa) and the density of seven understory species (Balfourodendron riedelianum, Chrysophyllum gonocarpum, E. leiocarpa, Holocalyx balansae, Machaerium stipitatum, Rhaminidium elaeocarpum, and S. dictyocarpa). These results probably reflect the outcome of a complex set of interactions including facilitation and competition, and further studies are necessary to better understand the magnitude and type of the effects of individual overstory species on understory species. The occurrence of species-specific associations shown here reinforces the importance of non-random processes in structuring plant communities and suggest that the influence of overstory species on understory species in high-diversity forests may be more significant than previously thought.